Tribology of abrasive machining processes - Marinescu, Ioan D. (William Andrew, 2013)
This book draws upon the science of tribology to understand, predict and improve abrasive machining processes. Pulling together information on how abrasives work, the authors, who are renowned experts in abrasive technology, demonstrate how tribology can be applied as a tool to improve abrasive machining processes. Each of the main elements of the abrasive machining system are looked at, and the tribological factors that control the efficiency and quality of the processes are described. Since grinding is by far the most commonly employed abrasive machining process, it is dealt with in particular detail. Solutions are posed to many of the most commonly experienced industrial problems, such as poor accuracy, poor surface quality, rapid wheel wear, vibrations, work-piece burn and high process costs. This practical approach makes this book an essential tool for practicing engineers. . Uses the science of tribology to improve understanding and of abrasive machining processes in order to increase performance, productivity and surface quality of final products. A comprehensive reference on how abrasives work, covering kinematics, heat transfer, thermal stresses, molecular dynamics, fluids and the tribology of lubricants. Authoritative and ground-breaking in its first edition, the 2nd edition includes 30% new and updated material, including new topics such as CMP (Chemical Mechanical Polishing) and precision machining for micro-and nano-scale applications.
Includes index.
Keywords: Grinding and polishing.; Tribology.; elektronické knihy; electronic books